DESIGN OF A CONTINUOUS SLIDING MODE CONTROLLER FOR THE ELECTRONIC THROTTLE VALVE SYSTEM (Journal of Engineering, 2011)
Lowering the emission, fuel economy and torque management are the essentialrequirements in the recent development in the automobile industry. The main engine controlinput that satisfies the above requirements is the throttling angle which adjusts the air massflow rate to the engine port. Due to the uncertainty and the presence of the nonlinearcomponents in its dynamical model, the sliding mode control theory is utilized in this workfor the throttle valve angle control system to design a robust controller for this system in thepresence of a nonlinear spring and Coulomb friction. A continuous sliding mode control lawwhich consists of a saturation function, instead of a signum function, and the integral ofanother saturation function is used in this work. This choice for the control structure willprevent the chattering to occurs but with a certain steady state error. On the other hand, theaddition of the integral term will effectively reduce the steady state error according to thechoice of its parameters. The simulations result for typical references of the opening throttleangle demonstrate the effectiveness of the proposed controller, especially after the addition ofa nonlinear integral term.